A missing piece in the Health for Peace agenda: gender diverse leadership and governance. (9th October 2022) - Meagher, Kristen; Mkhallalati, Hala; El Achi, Nassim; Patel, Preeti
Abstract : The purpose of this paper is to explore how gender diverse leadership and governance of health systems may contribute to the Health for Peace Agenda. Despite recent momentum, the evidence base to support, implement and evaluate 'Health for Peace' programmes remains limited and policy-makers in conflict settings do not consider peace when developing and implementing interventions and health policies. Through this analysis, we found that gender diverse leadership in health systems during active conflict offers greater prospects for sustainable peace and more equitable social economic recovery in the post-conflict period. Therefore, focusing on gender diversity of leadership and governance in health systems strengthening offers a novel way of linking peace and health, particularly in active conflict settings. While components of health systems are beginning to incorporate a gender lens, there remains significant room for improvement particularly in complex and protracted conflicts. Two case studies are explored, north-west Syria and Afghanistan, to highlight that an all-encompassing health systems focus may provide an opportunity for further understanding the link between gender, peace and health in active conflict and advocate for long-term investment in systems impacted by conflict. This approach may enable women and gender minorities to have a voice in the decision-making of health programmes and interventions that supports systems, and enables the community-led and context-specific knowledge and action required to address the root causes of inequalities and inequities in systems and societies.